Validity analysis of digital module based on generic science skills on environmental pollution topic for 10th grade students - Nurul Hidayati Utami; Kapsul Kapsul; Aminuddin Prahatama Putra; Jannah Jannah (Department of Biology Education, Universitas Pendidikan Indonesia, 2023)
The development of digital modules based on interesting generic science skills can be integrated in biology learning. Generic science skills (GSS) are related to skills through application and biological context. The factual and procedural knowledge obtained by students can be explored in the environmental pollution material because of various concepts and solve various real problems. This research is a descriptive study that explains the stages of digital module validation analysis based on generic science skills on environmental pollution for grade 10 high school students. Digital module validation test refers to five aspects such as (1) suitability of material, (2) presentation, (3) language, (4) generic science skills, and (5) visual/appearance. The subjects in the research at the initial review stage were three validators consisting of practitioners who are experts in learning biology and learning media. Based on the results of the study, it is known that the module developed as a whole is very valid in reference to aspects, namely the feasibility of the content aspect, the feasibility of the presentation aspect, the feasibility of the language aspect, the feasibility of the GSS aspect and the appearance, this shows that the digital module produced can be continued at the next stage.